O arquétipo do herói trovador no Kalevala e no filme Trovador Kerib, de Sergei Paradjanov - Almeida, Carolina Silva de (2019)
This research aims to compare and analyse the manifestation of the bard hero in the Finnish epic poem Kalevala and in the movie Ashik Kerib by Sergei Paradjanov. The reflexion upon the construction of this hero archetype allow us to understand this specific variation of the hero’s journey. The main aspect of the comparative analysis will be, therefore, the bard hero archetype. This thesis analyses and compares the construction of the characters on both works from the archetypical concept of hero and hero’s journey. The first of the two analysed works will be the Finnish epic poem Kalevala. The Kalevala was originally published in 1835 with a second expanded version in 1848. In this research we will focus only to the character Väinämöinen, son of the goddess Ilmatar. In his trips, Väinämöinen tries to free his land and his people from the curses and plagues of the sorceress Louhi, his archenemy. The second work is the film Ashik Kerib (1988) (literally: strange lover) directed by Sergei Paradjanov and Dodo Abashidze (co-director). The film is based on the tale of same name published in 1837 by the Russian writer Mikhail Lermontov. The tale comes from the Azerbaijani oral tradition, and narrates the story of a musician who is in love with the daughter of a rich merchant, who would only allow the marriage if the musician paid an adequate dowry in one thousand days. On both oeuvres, it is possible to perceive aspects of the hero’s journey, as well as the differences between the warrior hero’s journey and the bard hero’s journey, and specific cultural elements from the cultures that compound narratives.